Climate Change Impact on Aflatoxin Contamination Risk in Malawi's Maize Crops - Warnatzsch, Erika A.; Reay, David S.; Camardo Leggieri, Marco; Battilani, Paola (Frontiers in Sustainable Food Systems, 2020)
Malawi is one of the poorest countries in the world, with high levels of malnutrition and little domestic mycotoxin regulation. Domestically grown maize is the largest single source of calories in the country and a large contributor to the economy. This research uses Regional Climate Models (RCMs) to determine the climatic conditions in the three regions of Malawi (Northern, Central and Southern) in 2035 (2020-2049) and 2055 (2040-2069) as compared to the baseline climate of 1971-2000. This climatic data is then used as inputs to the Food and Agriculture Organization’s (FAO) AquaCrop model to assess the impact on the growth cycle of two maize cultivars varieties grown in each region and sown at three different times during the planting season. Finally, AFLA-maize, a mechanistic model, is applied to determine the impact of these projected changes on the aflatoxin B1 (AFB1) contamination risk. We find that Malawi’s climate is projected to get warmer (by 1-2.5°C) and drier (reduction of 0-4% in annual rainfall levels) in all regions, although some uncertainty remains around the changes in precipitation levels. These climatic changes are expected to shorten the growing season for maize, bringing the harvest date forward by between 10 and 25 days for the short-development variety and between 25 and 65 days for the long-development variety. These changes are also projected to make the pre-harvest conditions for Malawian maize more favorable for AFB1 contamination and risk maps for the studied conditions were drawn. Exceedances of EU safety thresholds are expected to be possible in all regions, with the risk of contamination moving northwards in a warming climate.